Arcs on speedskating straightaways: forces, energy and angular momentum - Nässén, N.; Nässén, H.-A.; Pendrill, A.-M. (Physics Education, 2022)
The 10 000 m speedskating event during the 2022 winter Olympics brought a new world record at 12 min and 30.74 s. In a document released after the competitions, the gold medalist Nils van der Poel describes his technique, including a focus on horizontal forces and a rapid sideways motion in connection with stride changes on the straight sections of the track (the `straightaways`). Based on a video of the race, together with his written description, we suggest that van der Poel makes use of the properties of angular momentum to increase his speed during a stride by a rapid inwards shift of the centre of mass.